THE INFLUENCE OF VINEYARD SOIL DEEP PLOWING AND FERTILIZATION ON GRAPE PRODUCTIVITY AND QUALITY (Scientific journal of the Fergana State University, 2025)
Because during the restoration of the plantation a significant part of the active roots was cut off, the work is carried out in rows for two years. In order not to damage the main roots of the vine, strips of at least 50 cm wide are left on each side of the row. It is very important that the blades of the central and side rippers are sharp, cut well and do not pull the root. During the restoration of the plantation, the root system of plants is significantly renewed. Removing some of the old roots during deep loosening of the soil increases the speed of movement of the rest of the root system, promotes the formation of more active small roots.